Nirmatrelvir/ritonavir Use With Tacrolimus in Lung Transplant Recipients: A Single-center Case Series. Issue 5 (28th October 2022) - Dewey, Katherine W.; Yen, Bo; Lazo, Jose; Seijo, Leslie; Jariwala, Ripal; Shah, Rupal J.; Quan, David; Carpenter, Bethanne; Paul Singer, Jonathan; Breen, Karen; Hays, Steven; Florez, Rebecca
Abstract : Background: Limited data and guidelines exist for using nirmatrelvir/ritonavir in solid organ transplant recipients stabilized on tacrolimus for the treatment of mild-to-moderate coronavirus disease. Concern exists regarding the impact of utilizing a 5-d course of nirmatrelvir/ritonavir with calcineurin inhibitors because of significant drug–drug interactions between ritonavir, a potent cytochrome P450 3A inhibitor, and other cytochrome P450 3A substrates, such as tacrolimus. Methods: We report the successful use of nirmatrelvir/ritonavir in 12 outpatient lung transplant recipients with confirmed severe acute respiratory syndrome coronavirus 2 infection stabilized on tacrolimus immunosuppression. All patients stopped tacrolimus and started nirmatrelvir/ritonavir 10 to 14 h after the last dose of tacrolimus. Tacrolimus was withheld and then reinitiated at a modified dose 48 h following the completion of nirmatrelvir/ritonavir therapy. Tacrolimus trough levels were checked during nirmatrelvir/ritonavir therapy and tacrolimus reinitiation. Results: Ten (10/12) patients were able to resume their original tacrolimus dose within 4 d of completing nirmatrelvir/ritonavir therapy and maintain therapeutic levels of tacrolimus. No patients experienced tacrolimus toxicity or acute rejection during the 30-d postcompletion of nirmatrelvir/ritonavir therapy. Conclusions: In this cohort of lung transplant recipients on tacrolimus, we demonstrated that nirmatrelvir/ritonavir can be safely used with close monitoring of tacrolimus levels and appropriate dose adjustments of tacrolimus. Further confirmatory studies are needed to determine the appropriate use of therapeutic drug monitoring and tacrolimus dose following completion of nirmatrelvir/ritonavir in the solid organ transplant population.